Currency Risk and Debt Maturity: Their Effects on the Resilience of Indonesia’s Foreign Exchange Reserves - Afriana, Wendra; Damanhuri, Didin S.; Taryono, Taryono; Amanah, Siti (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This study uncovers the unexpected negative impact of long-term external debt on Indonesia’s foreign exchange reserves, challenging conventional beliefs about debt stability. Research Objectives: This study provides important—and occasionally surprising—new insights into the dynamics of Indonesia's external debt and its impact on the country's foreign exchange reserves. Research Methods: Using recent time series data from 2013–2024 and the tried-and-true OLS regression method, this study provides a thorough and timely analysis of the relationship between Indonesia's foreign exchange reserves and the structure of its external debt. Empirical Results: The empirical results indicate that long-term debt has a negative impact on foreign exchange reserves, whereas Rupiah and foreign currency-denominated debts have positive effects. Notably, short-term debt shows no significant impact. These findings offer practical guidance for Indonesia’s external debt management, supporting better debt prioritization and enhanced financial resilience. Implications: These novel insights offer valuable guidance for optimizing debt management to strengthen Indonesia’s financial resilience and economic stability. JEL Classification: E4, E5, E6 How to Cite:Afriana, W., Damanhuri, D. S., Taryono.,& Amanah, S. (2025). Currency Risk and Debt Maturity: Their Effects on the Resilience of Indonesia’s Foreign Exchange Reserves. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 537-548. https://doi.org/10.15408/sjie.v14i2.46526.